Microplastic abundance, distribution, and composition in Sungai Dungun, Terengganu, Malaysia - Tee, Yang Hwi; Yusof Shuaib Ibrahim,; Wan Mohd Afiq Wan Mohd Khalik, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Scientific documentation on (Microplastics) MPs abundance in Malaysian waters is still limited and not fully understood. In this study, MPs occurrence in Sungai Dungun, Terengganu, Peninsular Malaysia was analysed. Sampling method was based on sieving 200 µm of bulk water to collect surface water samples from five sites in the vicinity of potential source for MP abundance. Characterisation of MPs was accomplished by gravimetric and digital image processing (for quantification and morphology categorisation), and chemical composition identified by attenuated total reflectanceFourier infrared spectroscopy. The range concentration of MPs was 22.8 to 300.8 items/m3 (mean 102.8 item/m3 ). It was recorded that most of the MPs found were black and transparent. The most frequent morphotypes were fibres, followed by fragments. Polypropylene (C3 H6 )n, polyacrylonitrile (C3 H3 N)n and rayon were the dominant polymertypes of MPs analysed in this work. Metals (Pb < As < Mn < Zn < Cu < Fe < Al) found within the MPs reported varied in terms of µg/mL. This study provided new insights into the understanding of MP levels in inland Malaysian freshwater environments